Navigating the spectrum of aggressiveness: Social dynamics and anxieties in tax planning - Brivot, Marion; Paquette, Suzanne; Huxley, Zachary (Accounting, Organizations and Society, 2025)
This qualitative inquiry investigates how tax professionals understand aggressiveness in tax planning and how they position themselves on the spectrum of aggressiveness. Based on semi-structured interviews with 33 experienced Canadian tax professionals from top-10 accounting and law firms, we find that tax professionals understand aggressiveness through a web of inter-related considerations. These include creativity, complexity, legal ambiguity, and lucrativeness, associated with risks of tax audits , technical errors, disputes with tax authorities over legal interpretations, and reputational damage for the client, the tax professional, and their firm. These considerations and related risks are often a source of anxiety for tax professionals. Drawing on contemporary philosopher Charlie Kurth's distinction between “punishment anxiety” and “practical anxiety,” we identify an intricate interplay between these two forms of anxiety and a collective deliberation process involving clients and colleagues, each bringing their own risk-reward preferences, which shapes professionals' decisions of how aggressive they should be. The socio-affective conceptualization of aggressiveness that we propose in this study contributes to the tax literature by deepening our understanding of the elusive concept of tax aggressiveness. It also enriches the broader literature on accounting and finance professionals' emotions at work by documenting the analytical value of a nuanced understanding of anxiety. Furthermore, it advances the professional ethics literature by highlighting the moral significance of practical anxiety in professional judgment about risky, ethically sensitive issues.